Desain Kebijakan Sistem Aplikasi Profil Desa dan Kelurahan: Studi Kasus Tata Kelola Data Digital pada Kementerian Dalam Negeri - Mohammad Noval (Research and Development Agency Ministry of Home Affairs, 2026)
This study explores the effectiveness of the Prodeskel policy design as a village data governance instrument that has not yet achieved maximum utilization, despite data validity being a central pillar for accurate development planning at the grassroots level. Utilizing a descriptive qualitative methodology, this research dissects the implementation process and operational constraints within the Directorate General of Village Government Development through a phenomenological approach to understand existing bureaucratic realities. Primary data were obtained through in-depth interviews with key stakeholders to ensure an analytical depth consistent with comprehensive public administration principles. The research findings confirm that low synchronization of policy instruments, dualism of inter-institutional roles, and limited technical competence among field officials constitute the primary obstacles to achieving an integrated data ecosystem. External factors, such as digital infrastructure deficits in remote areas, further weaken data accuracy and widen the digital divide between regions. As a policy implication, this study recommends a new policy design based on Michael Howlett’s policy instrument framework. This recommendation emphasizes policy instrument calibration, aligning the dimensions of technology, regulation, and organizational capacity coherently to create sustainable functional synergy. Furthermore, it highlights the need for strengthened oversight mechanisms and incentives for data managers at the village level to enhance work motivation and the quality of real-time data input. These insights are expected to serve as a strategic reference for the Ministry of Home Affairs in perfecting village data governance through a policy design that is more integrative, applicable, and responsive to the dynamics of digital governance in Indonesia.